Activation-free synthesis of nitrogen-doped biochar for enhanced adsorption of CO2. (25th June 2022) - Zhang, Junjie; Huang, Danru; Shao, Jingai; Zhang, Xiong; Yang, Haiping; Zhang, Shihong; Chen, Hanping
Abstract: Biochar is a renewable, low-cost carbon material with CO2 adsorption potential. The modification of biochar is of significance for enhanced CO2 adsorption and the high-value utilization of biochar. To make the modification process cleaner, in this study, a straightforward and activation-free synthetic strategy of nitrogen-doped porous carbon by co-carbonizing biochar and zeolitic imidazolate framework (ZIF-8) was demonstrated. The results showed that the nitrogen groups were uniformly introduced onto the surface of the biochar after modification. The interaction between biochar and ZIF-8 during thermal treatment improved the porosity of the products (especially the microporosity); this interaction became more significant with the increase of carbonization temperature. The surface area of biochar increased immensely from 3.0 to 989.3 m 2 /g, and its CO2 adsorption capacity increased from 0.52 to 2.43 mmol/g after modification (1 atm, 30 °C). Moreover, the density functional theory (DFT) calculation results show that the nitrogen and oxygen functional groups, especially C–O/CO and graphitic-N, have an obvious synergistic effect on CO2 adsorption and its CO2 adsorption performance is mainly dependent on the pores ranged from 0.62 to 0.72 nm. This work provides new insight into the design of modified biochar for CO2 adsorption. Graphical abstract: Image 1 Highlights: A clean and activation-free modification method of biochar was demonstrated. Micropores and nitrogen groups are introduced to biochar by heat treatment with ZIF-8. The surface area of biochar increased from 3.0 to 989.3 m 2 /g after modification. The CO2 adsorption capacity increased from 0.52 to 2.43 mmol/g (1atm, 30 °C). The pore size of 0.62–0.72 nm plays a decisive role in CO2 adsorption.